Childbirth Experiences and Delivery Care During Times of War: Testimonies of Syrian Women and Doctors - Bashour, Hyam; Kharouf, Mayada; DeJong, Jocelyn (Frontiers in Global Women's Health, 2021)
Background: Until the eruption of violence in 2011, Syria made good progress in improving maternal health indicators including reducing the maternal mortality ratio and increasing the level of skilled birth attendance. The war in Syria has been described as one of the worst humanitarian crises in recent times. Damascus Maternity Teaching Hospital is the largest maternity public hospital in the country that survived the war and continued to provide its services even during periods of pronounced instability. The main aim of this paper is to highlight the experience of childbirth and delivery care as described by women and doctors at times of severe violence affecting Damascus. Methods: This paper is based on secondary analysis of qualitative data collected between 2012 and 2014 for a WHO-funded implementation research project introducing clinical audits for maternal near-misses. This analysis specifically looked at the effects of violence on the childbirth experience and delivery care from the perspective of both women and physicians. A total of 13 in-depth interviews with women who had recently delivered and survived a complication and 13 in-depth interviews with consultant obstetricians were reviewed and analyzed, in addition to three focus group discussions with 31 junior care providers. Results: Three themes emerged concerning the experiences of women and doctors in these times of war. First, both women and doctors experienced difficulty reaching the hospital and accessing and providing the services, respectively; second, quality of care was challenged at that time as perceived by both women and doctors; and third, women and doctors expressed their psychological suffering in times of hardship and uncertainty and how this affected them. Conclusions: Efforts to safeguard the safety of delivery and prevent maternal mortality in Syria continued despite very violent and stressful conditions. Both women and providers developed strategies to navigate the challenges posed by conflict to the provision of delivery care. Lessons learned from the experiences of both women and doctors should be considered in any plans to improve maternal healthcare in a country like Syria that remains committed to achieving the Sustainable Development Goals in 2030 in the aftermath of nearly 10 years of war.